Efeitos do envelhecimento e da integridade funcional do córtex pré-frontal sobre a memória contextual e uso de estratégias de codificação - Barragana, Vânia Jofré (2011)
Background: Age related reductions in contextual memory can impair daily functioning of older adults and have an important impact on their quality of life. Thus, the understanding of the neurobiological correlates of this memory decline is important to the establishment of effective cognitive interventions in healthy older adults. Objective: The current study was aimed to investigate the effects of aging and prefrontal cortex (PFC) function on contextual memory performance under different encoding conditions in a naturalistic experimental paradigm. Methods: Young (n=34, aged 20 - 35 years) and older adult men (n=31; aged 54 - 87 years) matched for education completed a recognition memory task for context (location of objects depicted in different rooms of a house) with or without an incidental binding cue at encoding. In addition, Wisconsin Card Sorting Test (WCST) was carried out to assess PFC function. Results: Results for contextual memory performance showed significant main effects of aging and encoding condition. Older adults performed significantly poorer than young controls in the encoding condition without incidental binding cue. The introduction of the incidental binding cue at encoding significantly improved the context recognition scores in young and older adults. A significant association between WCST scores and the performance for contextual memory were found only in the task without binding cue and just for the older adult men. Conclusion: The main findings indicate that the age related deficits on contextual memory are associated to age related impairments of PFC function, as indicated by the WCST. However, contextual memory of older adults improved with cognitive support at encoding and became independent of the scores on WCST, suggesting that incidental associative binding instructions at encoding can mitigate PFC deficits.